Feeding the body politic: metaphors of digestion in Progressive Era US immigration discourse - Councilor, KC (Communication and Critical/Cultural Studies, 2017)
In the era between the 1882 Chinese Exclusion Act and the Immigration Act of 1924, nativist advocates for immigration restriction commonly invoked metaphors of eating and digestion to support their cases. This essay draws on political, popular, and scientific discourses around immigration and digestion in order to analyze the affective power of the rhetorically constructed “body politic.” While numerous scholars have addressed the ways immigrants have been variously figured as threats to the nation—as pollutants, toxins, disease, floods, or invading armies—few have analyzed metaphors of eating and digestion. I argue that the national body became a metonym for the ideal (white) citizen body, which supported anti-immigrant rhetoric through metaphors of eating, digesting, and eliminating undesirable aliens—those who did not agree with the national stomach. The body politic came to represent the ideal US American body as individuals were invited to identify with the nation through the trope of the body politic; immigrants who did not share this ideal body were rendered undesirable through their association with indigestibility and disgust. This essay demonstrates the affective and thus political power that digestion metaphors provided, shedding light on an early instantiation of the disgust that pulses through twenty-first-century anti-immigrant discourse in the United States.
15 citations (Crossref) [2023-10-31]
Keywords: dept.com; digestion; immigration; nativism; race; rhetoric